Dipturus nidarosiensis - Ebert, David A.; Wintner, Sabine P.; Kyne, Peter M. (Zenodo, 2021)
Dipturus nidarosiensis (Storm, 1881) Norwegian Skate Raja nidarosiensis Storm, (ex Collett) 1881: 80. Syntypes: ZMUO J6339 (1 stuffed in poor condition), ZMUO (2, lost). Type locality: Munkholmen, Trondheim Fjord, Norway. Local synonymy : Raja ( Dipturus ) springeri : Compagno et al ., 1989: 92, pl. (in part); Compagno et al ., 1991: 96 (in part). Dipturus springeri : Compagno, 1999: 116 (in part); Compagno & Ebert, 2007: 139, fig. 6e (in part); Ebert et al ., 2008: 88 (in part); NPOA, 2013: 56 (in part); da Silva et al ., 2015: 247 (in part); Ebert, 2015: 176, fig. 195 (in part?); Ebert & van Hees, 2015: 147 (in part). Dipturus nidarosiensis : Ebert & Compagno, 2007: 119; Last et al ., 2016f: 21; Last et al ., 2016g: 266, fig. 19.57. South Africa voucher material : Uncertain, all previous large Dipturus species off the west and south coasts of South Africa have been referred to as D. springeri . The specimens listed here were all from the west and south coasts of South Africa and may be D. nidarosiensis pending re-examination: SAIAB 26001, SAIAB 26231, SAIAB 26466, SAIAB 26467, SAIAB 26468, SAIAB 26636, SAIAB 26637, SAIAB 26912, SAIAB 26913, SAIAB 26914, SAIAB 40953. South African distribution : West coast and possibly south coast (WC), but eastern extent of range uncertain due to confusion with D. springeri . Remarks : This species was thought to be restricted to the northeast Atlantic, but Last et al . (2016a), based on molecular data, extended its range to South Africa where it has been misidentified with D. springeri , which now may only occur off the east coast of South Africa. A re-examination of South African D. springeri specimens is required to better define the geographic distribution of these two large Dipturus species. Conservation status : NT (2015). Published as part of Ebert, David A., Wintner, Sabine P. & Kyne, Peter M., 2021, An annotated checklist of the chondrichthyans of South Africa, pp. 1-127 in Zootaxa 4947 (1) on page 80, DOI:10.11646/zootaxa.4947.1.1, ...